The Continuing Relevance of the Myth of American Exceptionalism to the Current American Political Practice - Selma BERKANE, Boutheyna BOUABDALLAH (My University, 2019)
The present dissertation is intended to investigate exceptionalism in American society and politics. The method that is used in this study is the historical analytical approach. It aims at providing the necessary information to understand the impact of exceptionalism on the American society and politics. Therefore, this work is meant to provide a clear analysis of the main events and facts that contributed to the transformation of American’s thoughts and make it exceptional. For instance, indicating the idea that the United States is a nation qualitatively different from the rest of the world, with a mission and responsibility to lead the world to democracy and freedom. It has been the focus of numerous studies within the fields of United States’ history and foreign affairs, as well as international relations. While the body of work on American Exceptionalism is extensive, the exact usages, purposes, and implications of the notion on US policies, as well as its role in the United Nations, is unfortunately still unexplored.
Keywords: Keywords : American exceptionalism - Americans thoughts – American politics – National identity - International relation – US poli